Macrophage membrane- and cRGD-functionalized thermosensitive liposomes combined with CPP to realize precise siRNA delivery into tumor cells - Jingxue Nai; Jinbang Zhang; Jiaxin Li; Hui Li; Yang Yang; Meiyan Yang; Yuli Wang; Wei Gong; Zhiping Li; Lin Li; Chunsheng Gao (Elsevier, 2022)
Despite the success of small interfering RNAs (siRNAs) in clinical settings, their fast clearance and poor delivery efficiency to target cells still hinder their therapeutic effect. Herein, a new treatment system was constructed by combining thermosensitive liposomes with the macrophage membrane, tumor-targeting cyclic Arg-Gly-Asp peptide, a cell-penetrating peptide, and thermotherapy. The constructed system was found to be thermosensitive and stable; the proteins were inherited from the macrophage membrane. This new system combined with thermotherapy displayed the least uptake by macrophages, the greatest uptake by HepG2 cells, the most obvious HepG2 cell apoptosis, and the strongest inhibition of Bcl-2 mRNA and Bcl-2 protein in HepG2 cells. Moreover, 24 h after system administration in tumor-bearing mice, the most prominent distribution of siRNA was observed in tumors, while almost no siRNA was found in other organs. The strongest inhibition of Bcl-2 mRNA, Bcl-2 protein, and tumors was found in mice that had received the proposed system. In summary, when using the constructed system both in vitro and in mice, less uptake by the reticuloendothelial system, greater accumulation in tumor cells, and improved therapeutic efficacy were observed. Therefore, this new system can deliver siRNA selectively and efficiently, and it is a promising therapeutic candidate for precise tumor-targeted therapy.